Scaling-Up Cervical Cancer Screening and Treatment in Sub-Saharan Africa: Perspectives From Local Health Policymakers - DANGBEMEY, Djima Patrice; HOUNKPATIN, BENJAMIN IGNACE B.; Khazraji, Youssef Chami; Bennani, Maria; DANGBEMEY, D. Patrice (My University, 2023)
In September 2022, we published in the JCO Global Oncology the results of a pilot project on cervical cancer screening using the screen-and-treat approach within the existing primary health care services in sub-Saharan Africa (the CARE4Afrique project). The project was led by the International Agency for Research on Cancer (IARC-WHO) and supported by the Lalla Salma Foundation for Cancer Prevention and Treatment (LSF).1 The article presented the findings of three countries (Benin, Cote d ˆ ’Ivoire, and Senegal) although since the publication, a fourth country (Cameroon) was included in the project. We reported that opportunistic screening using visual inspection with acetic acid (VIA) and immediate treatment of eligible precancerous lesions with thermal ablation was feasible and acceptable with minimal side effects. The CARE4Afrique project was completed in 2021, and we wanted to learn from the local decisionmakers whether the lessons learnt from the pilot project had improved cervical cancer screening in their country. In January 2023, we conducted in-depth interviews of representatives of the Ministry of Health (MoH; health officers and clinicians) of the four countries to understand the challenges they faced during the project implementation. We also inquired whether they were considering or have already scaled up screening and treatment at the primary health centers in the light of the results of the pilot project. Finally, we asked whether they were considering the use of human papillomavirus (HPV)-DNA as a primary screening test, as recently recommended by the WHO.
Keywords: scaling up cervical cancer; sub saharan africa